Unpacking Youth Agency in Community-Based Rural Tourism: Student Perceptions and Sustainable Development Strategies in the Tabagsel Region, Indonesia - Icol Dianto; Zilfaroni; Halim Mokhtar (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2026)
Community-based rural tourism is increasingly recognized as a pathway for sustainable development, cultural preservation, and local economic resilience in developing countries. However, limited studies have examined how educated youth perceive rural tourism development in culturally rich but digitally marginalized destinations. This study explores university students’ perceptions of rural tourism resources, development challenges, and sustainable strategies in the Tabagsel region of North Sumatra, Indonesia. A descriptive qualitative approach was employed through semi-structured in-depth interviews with eight university students originating from tourism- potential villages across the region. The interview data were analyzed using thematic analysis to identify recurring patterns in participants’ perspectives. The findings revealed three major themes. First, students considered natural landscapes, cultural heritage, and community- based resources as key assets for sustainable rural tourism. Second, they identified inadequate infrastructure, limited institutional collaboration, and weak digital promotion as major barriers to tourism development and youth participation. Third, students supported environmental sustainability and community empowerment while acknowledging the need for selective modernization, reflecting the balance between preserving rural authenticity and meeting contemporary tourism demands. This study demonstrates that youth perspectives are valuable for participatory rural tourism planning and can contribute to strengthening sustainable community-based tourism initiatives in developing regions.